Ecological study on the use of hormonal contraception, abortions and births among teenagers in the Nordic countries - Hognert, Helena; Skjeldestad, Finn Egil; Gemzell-Danielsson, Kristina; Heikinheimo, Oskari; Milsom, Ian; Lidegaard, Øjvind; Lindh, Ingela (BMJ Open, 2018)
Published version, available at: https://bmjopen.bmj.com/content/8/10/e022473.full The DOI does not function. Objectives Compare hormonal contraceptive use, birth and abortion rates among teenagers in the Nordic countries. A secondary aim was to explore plausible explanations for possible differences between countries. Design Ecological study using national registry data concerning births and abortions among all women aged 15–19 years residing in Denmark, Finland, Iceland, Norway and Sweden 2008–2015. Age-specific data on prescriptions for hormonal contraceptives for the period 2008–2015 were obtained from national databases in Denmark, Norway and Sweden. Setting Denmark, Finland, Iceland, Norway and Sweden. Participants Women 15–19 years old in all Nordic countries (749 709) and 13–19 years old in Denmark, Norway and Sweden (815 044). Results Both annual birth rates and abortion rates fell in all the Nordic countries during the study period. The highest user rate of hormonal contraceptives among 15–19-year-olds was observed in Denmark (from 51% to 47%) followed by Sweden (from 39% to 42%) and Norway (from 37% to 41%). Combined oral contraceptives were the most commonly used methods in all countries. The use of long-acting reversible contraceptives (LARC), implants and the levonorgestrel-releasing intrauterine systems, were increasing, especially in Sweden and Norway. In the subgroup of 18–19-year-old teenagers, the user rates of hormonal contraceptives varied between 63% and 61% in Denmark, 56% and 61% in Norway and 54% and 56% in Sweden. In the same subgroup, the steepest increase of LARC was seen, from 2% to 6% in Denmark, 2% to 9% in Norway and 7% to 17% in Sweden. Conclusions Birth and abortion rates continuously declined in the Nordic countries among teenagers. There was a high user rate of hormonal contraceptives, with an increase in the use of LARC especially among the oldest teenagers.